Spectroscopic study of defects in cadmium selenide quantum dots (QDS) and cadmium selenide nanorods (NRS) - Roy, Santanu (Kansas State University, 2013)
Ever depleting sources of fossil fuel has triggered more research in the field of alternate sources of energy. Over the past few years, CdSe nanoparticles have emerged as a material with a great potential for optoelectronic applications because of its easy exciton generation and charge separation. Electronic properties of CdSe nanoparticles are highly dependent on their size, shape and electronic environment. The main focus of this research is to explore the effect of different electronic environments on various spectroscopic properties of CdSe nanoparticles and link this to solar cell performance. To attain that goal, CdSe quantum dots (QDs) and nanorods (NRs) have been synthesized and either doped with metal dopants or embedded in polymer matrices. Electronic properties of these nanocomposites have been studied using several spectroscopic techniques such as absorption, photoluminescence, time-resolved photoluminescence, confocal microscopy and wide field microscopy. Indium and tin are the two metal dopants that have been used in the past to study the effect of doping on conductivity of CdSe QDs. Based on the photoluminescence quenching experiments, photoluminescence of both indium and tin doped samples suggest that they behave as n-type semiconductors. A comparison between theoretical and experimental data suggests that energy levels of indium doped and tin doped QDs are 280 meV and 100 meV lower than that of the lowest level of conduction band respectively. CdSe nanorods embedded in two different polymer matrices have been investigated using wide field fluorescence microscopy and confocal microscopy. The data reveals significant enhancement in bandedge luminescence of NRs in the vicinity of a conjugated polymer such as P3HT. Photoactive charge transfer from polymers to the surface traps of NRs may account for the observed behavior. Further study shows anti-correlation between bandedge and trap state emission of CdSe NRs. A recombination model has been proposed to explain the results. The origin of traps is also investigated and plausible explanations are drawn from the acquired data.
Keywords: Spectroscopy of defects; Chemistry (0485)